Comparisons of wavelets and contourlets for vibration-based damage identification in the plate structures. Issue 7 (May 2019) - Vafaie, Sepideh; Salajegheh, Eysa
The objective of the present study is to compare a new approach based on contourlet transform and a traditional method based on wavelet transform to demonstrate curve damages in plate structures. The contourlet transform approach, as a novel two-dimensional development of wavelet transform, was extended to deal with inherent restrictions of wavelets. According to previous studies, wavelets have indicated poor performance to detect curve damages due to its basic elements. Therefore, this study utilized contourlet transform as a new method having an efficient performance to display this kind of discontinuities. In this research, contourlet transform and wavelet transform have been applied to a plate using four fixed boundary conditions including circle damages with arbitrary specifications and location in order to demonstrate their performance in damage identification. Comparing damage shape attained from contourlet transform and wavelet transform, it was revealed that contourlet transform could be utilized as an accessible and useful technique to detect damage with curvature.